Synthesis, characterization and antibacterial screening of some Schiff bases derived from pyrazole and 4-amino antipyrine (2016)
Some Schiff bases of pyrazole and 4-amino antipyrine have been synthesized. The antibacterial screening of these synthesized compounds was done in dimethyl forma-mide against four Gram positive bacteria viz. Bacillus cereus, Staphylococcus aureus, Staphylococcus epidermidids and Micrococcus luteus, and three Gram negative bacteria viz. Proteus mirabilis, Escherichia coli and Klebsiella aerogenes. It is observed that in comparison to Schiff bases of 4-amino antipyrine, pyrazole Schiff bases are better for inhibition for these selected Gram positive and Gram negative bacterial strains.